The Making of a Market: The Relational Aspects of Credit Card Installments in Turkey - Muhammed Fatih Karakaya (İstanbul Üniversitesi Sosyoloji Dergisi)
With over 80 million credit cards, the Turkish credit card market is one of the largest in Europe. As of July 2021, the total annual volume of credit card sales exceeded 588 billion Turkish lira. Installment payments are the most popular form of credit card purchase in Turkey, with 40% of all transactions being installment purchases. The history of the credit card installment market can be traced back to the late 1990s when certain non-procedural –if not fraudulent– point-of-sale level transactions forced banks to launch an installment feature for their credit cards. Although few countries have credit cards with such a feature, this did not emerge from an innovative strategy of a Turkish bank. Instead, “The market gave banks the order to issue such a credit card to be operated in installment purchases,” as stated by the vice president of one of Turkey’s largest commercial banks. Installment sale as a century-old buy-on-credit pattern has allowed a new market device to take part in the polyadic relation of sale and debt until forming a hybrid pattern of buying on credit. Thus, employing the actor-network theory approach for a historical sociology of credit card installments market in Turkey provides a relational explanation for analyzing the emergence of markets. Such an explanation includes the dialectical relations between existing and emerging economic patterns as well as between the relevant parties performing in the processes of making a market.